Republic of Kazakhstan : 2019 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation with Republic of Kazakhstan discusses that the political transition has increased the focus on social conditions and regional and rural development. Discussions focused on enhancing the inflation-targeting framework, bank soundness, the fiscal framework, structural reforms, and governance. Growth has been buoyed by new spending, retail credit, and oil and gas investments. Inflation has picked up, and the current account has deteriorated. High domestic demand driven by major oil and gas investments and government and household consumption supported by wage increases and consumer lending has underpinned the economy's strong performance. The state continues to play a strong role in the economy, and the authorities face challenges ensuring that measures are well targeted and effective in promoting private sector growth. The challenges include oil volatility and dependency, reliance on subsidies and other state support, still-impaired banks, and governance vulnerabilities. Progress is being made with structural reform implementation, with many of the flagships '100 Concrete Steps' completed and the remaining ones broadly on track. Efforts to promote a smaller state footprint should continue, with actions to improve governance and mitigate corruption vulnerabilities.